Entre togas e grilhões: o acesso à justiça dos escravizados no Maranhão oitocentista (1860-1888) - Assis, Victor Hugo Siqueira de (2020)
The present work has as main objective to investigate how has constituted the access to justice of the enslaved in the province of Maranhão in the second half of the nineteenth century. Thus, the perspective that this research proposes is to understand the law as a space for discussion and appropriation, verifying how the social actors of the imperial period made use of this system. To this end, in view of the fact that judicial proceedings are a rich historical source in the search for the reconstruction of social conflicts of a certain time, several types of lawsuits involving enslaved people in the Alcântara, Guimarães and Viana counties, from 1860 to 1888, were examined in the Maranhão State Court Archives. From this material, we initially explore the legal-legislative evolution and the way in which the legal system was structured from the colonial period to the end of the Empire, both with regard to Brazilian state as in relation to Maranhão. Once this context is established, it is compared how the institute of slavery fitted into this dynamic and how slaves were treated by the legal sphere. At this point, the legal status of captives and the apparent paradox of being considered both thing and person are debated. Once the legal personality of the enslaved is acknowledged, albeit in a limited way, the discussion goes on about the possibility of the captives having a right of action. In the second part of the study, we discuss how this right was exercised, using the observation of the main purpose sought by the captives when they resorted to justice: the search for freedom. This examines the use of the justice system as a viable option in manumission efforts. In the final part, we discuss the judicial mechanisms used by the masters in order to reduce to captivity those who enjoyed their freedom, demonstrating that the slave system was not willing to surrender easily to the liberating inflows. However, it is clear that justice has also been managed by freedmen, family members and their support networks in order to avert the risks of returning to captivity or reducing it from those who had never experienced it, consolidating the legal arena as an important locus in discussions around the institute of slavery.